Improving Weed Control Efficiency through Remote Sensing and Proper Selection of Nozzle Type and Application Rate - Vasić, Filip; Sedlar, Aleksandar; Turšijan , Lazar (Acta herbologica, 2025)
This study explores the integration of unmanned aerial vehicle (UAV) technology with optimized herbicide application techniques to enhance weed control efficiency. A field trial was conducted in maize (Zea mays L.) in the 4–6 leaf stage (BBCH14-16), combining pre-treatment multispectral drone imaging with variable nozzle types and spray volumes. Weed maps generated from UAV data enabled targeted application, while deposition was measured using a fluorescent tracer and spectrophotometric analysis. Results showed that TD-ADF twin nozzles achieved the highest deposition efficiency, especially at lower spray volumes (133–155 L/ha), without compromising herbicide delivery. The study also found that reduced spray volumes can maintain or even improve deposition when paired with proper nozzle selection and application speed. Findings support the use of low-volume, precision spraying systems guided by remote sensing to reduce input costs and environmental impact, while maintaining or improving weed control efficacy. This integrative approach aligns with the goals of sustainable and precision agriculture.
Keywords: remote sensing, drone, sprayers, deposit, weeds, precision agriculture